2022
DOI: 10.3390/ijms23147527
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antibiofilm, and Antiviral Farnesol-Containing Nanoparticles Prevent Staphylococcus aureus from Drug Resistance Development

Abstract: Multidrug antimicrobial resistance is a constantly growing health care issue associated with increased mortality and morbidity, and huge financial burden. Bacteria frequently form biofilm communities responsible for numerous persistent infections resistant to conventional antibiotics. Herein, novel nanoparticles (NPs) loaded with the natural bactericide farnesol (FSL NPs) are generated using high-intensity ultrasound. The nanoformulation of farnesol improved its antibacterial properties and demonstrated comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In vitro, the scavenging effect of some disinfectants on biofilms has been studied. A high concentration of farnesol (30 mM) shows antimicrobial properties against bacterial biofilms [ 36 , 37 ]. Hypochlorous acid, a powerful disinfectant, can break bacterial biofilms and may be useful in the treatment of orthopaedic fixative infections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the scavenging effect of some disinfectants on biofilms has been studied. A high concentration of farnesol (30 mM) shows antimicrobial properties against bacterial biofilms [ 36 , 37 ]. Hypochlorous acid, a powerful disinfectant, can break bacterial biofilms and may be useful in the treatment of orthopaedic fixative infections [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the polyprenol salvage pathway was first observed more than 25 years ago, but the enzymes responsible in animals or any pathogen are still unident ified [72,80]. Despite this, the interest in this pathway for the treatment of several human pathologies, ranging from osteonecrosis to infectious diseases, is increasing [92,93]. As a consequence, it is impractical to mention here everything published in this field, and we needed to make a selection of those reports that best illustrated the topics discussed, with a focus on biomedical problems.…”
Section: Biomedical Importance Of the Geranylgeraniol And Farnesol Sa...mentioning
confidence: 99%
“…Farnesol can also interfere with the rate of glycan synthesis in the biofilm matrix, impairing biofilm establishment. 20,21 For example, in Streptococcus mutans, momentary exposure to farnesol influenced the growth and metabolism of bacteria by disturbing the bacterial membrane and elevating the polysaccharide content within streptococcal biofilms. 20 Studies focused on the mode of action of terpenic alcohols (including farnesol) on Staphylococcus aureus suggested that cell membrane damage may be one of the main antibacterial mechanisms.…”
Section: Introductionmentioning
confidence: 99%